THE WAR ON DRUGS 2.0: DARKNET FENTANYL'S RISE AND THE EFFECTS OF REGULATORY AND LAW ENFORCEMENT ACTION. - Miller, Jacob N. (Contemporary Economic Policy, 2020)
U.S. overdose deaths attributed to synthetic opioids, such as fentanyl, have increased from under 3,000 in 2013 to nearly 20,000 in 2016, making up half of all opioid‐related overdose deaths. Using web scrapes of darknet markets from 2014 to 2016, I provide historical prices for fentanyl and its most popular analogues and find that fentanyl vendors priced fentanyl in 2014 at a 90% discount compared to an equivalent dose of heroin. Using regression discontinuity, I evaluate the effects of two major law enforcement and regulatory events. I find minimal lasting effects of U.S. legal actions intended to disrupt darknet markets, but there are statistically significant indications of a price increase corresponding with regulatory action in China. Despite these indications of some regulatory success, fentanyl prices remained approximately 90% cheaper than heroin.